The mask methodology and knowledge books - Ermine, Jean-Louis; Bedford, Denise; Garcia-Perez, Alexeis (Emerald Publishing Limited, 2025)
The Mask Methodology and Knowledge Books enables an organization to develop knowledge books, which have proven to be easy to use, easy to store, find and manage, and easy to update as organizational knowledge changes. They have also proven to be highly effective self-study and training resources. Until now, application of the methodology has been limited to Europe - specifically French speaking countries, because the source documentation and in person training materials have not yet been translated to languages other than French. This compelling new contribution to the field comprises of: A review the types of knowledge capital, and highlight the critical role of tacit knowledge in business operations; an introduction to the economic context for identifying and valuing critical business knowledge; and explanation of the relationship of knowledge engineering to MASK (Method for Analyzing and Structuring Knowledge); a outline of the six models that comprise the MASK model; an explanation of the importance of focusing on expertise that is well recognized by and essential to an organization; instruction on how to design a Knowledge Book for self-study and training; and a guide to building a governance and maintenance process for knowledge books.
Includes index.
Keywords: Tacit knowledge.; Industrial management.; Business & Economics -- Management.; Office management.; Management and management techniques.; elektronické knihy; electronic books